Evaluation of clinical outcomes following conventional right flank and laparoscopic ovariectomy in female dogs - D., Vilas; Tanwar, Mahendra; Palecha, Sakar; Kachwaha, K.; Sharma, M.L.; Bishnoi, P. (Indian Journal of Veterinary Surgery, 2025)
A study was conducted on 12 female dogs to compare the outcomes of conventional and laparoscopic ovariectomy techniques. The animals were randomly divided into two equal groups: group A underwent conventional right flank ovariectomy, while group B underwent laparoscopic ovariectomy using a threeport technique. All procedures were performed under a standardized anaesthetic protocol. No significant differences were observed in vital parameters such as heart rate, respiratory rate, and rectal temperature between the groups. In both groups, no significant changes were seen in blood glucose levels pre- and postoperatively. Postoperative serum cortisol levels and pain scores increased non-significantly in both groups; however, group A consistently demonstrated higher cortisol concentrations and pain scores than group B. The duration of surgery was significantly (P